Hiroshima, 6th August 1945 - Hook, Jason (London : Hodder Children's Books, 2002)
Examines the events leading up to the bombing of Hiroshima on August 6, 1945, the day itself, and the ways in which people learned to live afterwards.
Includes index.
Keywords: Atomic bomb; Hirsohima-shi -- Japan -- 1945 -- History; World war -- 1939-1945 -- Japan -- Hiroshima-shi.